2015
DOI: 10.1086/679700
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Roles for Histone Deacetylases in Pulmonary Hypertension and Right Ventricular Remodeling (2013 Grover Conference series)

Abstract: Reversible lysine acetylation has emerged as a critical mechanism for controlling the function of nucleosomal histones as well as diverse nonhistone proteins. Acetyl groups are conjugated to lysine residues in proteins by histone acetyltransferases and removed by histone deacetylases (HDACs), which are also commonly referred to as lysine deacetylases. Over the past decade, many studies have shown that HDACs play crucial roles in the control of left ventricular (LV) cardiac remodeling in response to stress. Sma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 94 publications
0
33
0
Order By: Relevance
“…Few studies have reported the beneficial effects of small molecule inhibitors of class I HDACs in preclinical models of LV and RV failure, blocking pathological cardiac hypertrophy and fibrosis and improving ventricular function [25]. Contrary to initial findings of the beneficial effects of HDAC inhibition using VPA on pulmonary artery banding (PAB) or MCT-induced cardiac hypertrophy [26] and trichostatin A (TSA) on transverse aortic constriction-induced cardiac hypertrophy [27], BOGAARD et al [28] reported detrimental effects of TSA and VPA treatment in PAB-induced RV hypertrophy.…”
Section: Mixed Results Of Hdac Inhibition In the Right Ventriclementioning
confidence: 99%
“…Few studies have reported the beneficial effects of small molecule inhibitors of class I HDACs in preclinical models of LV and RV failure, blocking pathological cardiac hypertrophy and fibrosis and improving ventricular function [25]. Contrary to initial findings of the beneficial effects of HDAC inhibition using VPA on pulmonary artery banding (PAB) or MCT-induced cardiac hypertrophy [26] and trichostatin A (TSA) on transverse aortic constriction-induced cardiac hypertrophy [27], BOGAARD et al [28] reported detrimental effects of TSA and VPA treatment in PAB-induced RV hypertrophy.…”
Section: Mixed Results Of Hdac Inhibition In the Right Ventriclementioning
confidence: 99%
“…SAHA has been shown to inhibit the deacetylase activity of HDAC1, 2, 3, 6, 8 (27). HDAC1 was confirmed that it's the strongest deacetylase to deacetylate Smad7 (11 Figure 4A) in a time-dependent manner.…”
Section: Saha Suppressed Tgf-β1-induced Hadac1 Activity In Vitromentioning
confidence: 89%
“…Indeed, estrogen through ERβ can activate the modulatory calcineurin-interacting protein 1 gene blocking calcineurin activation in myocytes 22 . Histone deacetylase (HDACs) are important in regulation of cardiac hypertrophy: class II is involved in signaling that inhibit this disorder, whereas class I promotes hypertrophy 106 . Recently, Pedram at al demonstrated that angiotensin regulates gene and protein level of both class I and II HDACs and rapid estrogen action through ERβ blocks these angiotensin actions 107 .…”
Section: Membrane Delimited (Non-genomic) Signalingmentioning
confidence: 99%